Cytokine measurement in lymphocyte culture supernatant of inactive lepromatous leprosy patients - Fulya, I.; Mehmet, O.; Handan, A.; Vedat, B. (Medknow Publications and Media Pvt. Ltd, 2006)
The aim of the present study was to determine the effects of stimulation of sonicated Mycobacterium leprae (MLS) extract and phorbol myristate acetate (PMA) on the pattern of cytokine production in peripheral blood mononuclear cells (PBMC) and to find out whether there is any difference between stimulation of MLS extract and PMA. Blood samples were collected and PBMC isolated from 43 inactive lepromatous leprosy patients. After culture for 24 hours, lymphocytes were stimulated with MLS extract and PMA. In the culture supernatant, IL-2, 4, 6, 8, TNF-alpha and TGF-beta levels were measured by using ELISA. M. leprae stimulated group IL-6, IL-8, TNF-alpha, TGF-beta levels were found significantly higher than PMA stimulated group (P<0.05). However, there was no difference between the two groups for IL-4. Only IL-2 levels were higher in PMA stimulated group than M. leprae stimulated group. Sonicated M. leprae extract have a strong effect on cytokine levels in vitro. Our results suggest that antigens with varying specificities favour the production of distinct cytokine patterns following in vitro restimulation.
Keywords: Cytokines; Leprosy; Peripheral blood mononuclear cells